UAV - Multispectral orthomosaic from Nybygget, 2018-04-25 - Asa Research Station (Swedish University of Agricultural Sciences, 2021)
Near-ground multispectral orthomosaics collected from UAV platforms, by means of mulstispectral cameras containing red, green, red edge and NIR bands. Nominal pixel resolution is 5 cm.
Asa Research Station (2021). UAV - Multispectral orthomosaic from Nybygget, 2018-04-25 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/iP7O4NANrd6bgFT-864JSqvU
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap